The Basolang Tradition of the Talang Mamak Tribe as the Caring of Environmental Value in Science Learning and the Project to Strengthen the Pancasila Students Profile - Putra, M. Jaya Adi; Susilawati, Susilawati; Bin Ali, Mohd Norawi (Journal of Natural Science and Integration, 2022)
The basolang tradition is a tradition of the Talang Mamak tribal community. The basolang tradition describes how people work together to use nature as a material for cultivating needs. The purpose of this study was to analyze the basolang tradition of the Talang Mamak Tribe as a value of caring for the environment and the Riau Province Pancasila Student Profile Strengthening Project for elementary school students. This value will be a reference for educators as a project to strengthen the Pancasila student profile in Riau Province. The type of research used in this study is an ethnographic research method which is included in qualitative research. The data sources in this study were elementary school students, traditional elders, community leaders, and the Talang Mamak indigenous community. Data collection methods used are observation, interviews, and documentation. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of this study show that there is an environmental care value that can be taken from the basolang tradition for elementary school students.  This is as obtained by researchers, including elementary school students can have attitudes and actions to prevent environmental damage and make good use of the natural environment. In addition, the values in the basolang tradition also contain pancasila profile values such as piety to God Almighty, noble character, and cooperation. This value can later be used as a reference for educators in Riau province as a project to strengthen the profile of Pancasila students.Keywords: basolang tradition, the value of caring for the environment, the profile of pancasila students.